Mechanism of the effect of TREM2 on cognitive function in autistic mice: TREM2 on cognitive function - Tian, Yi; Ai, Rong; Xiao, Xiao; Liu, Weiliang; Cheng, Shanqing; Zhu, Xiaoping (Cellular and Molecular Biology, 2024)
This study aimed to investigate the mechanism of the effect of TREM2 on cognitive function in autistic mice. TREM2 overexpression and knockdown viruses were given to autism spectrum disorder (ASD) mice and BV2 microglia cell line. To assess cognitive performance, all groups of mice took part in the open field, new object recognition, Morris water maze, and three-box social experiments. Double immunofluorescence labeling demonstrated co-localization of LC3II and NeuN. Proteins from the PI3K/Akt/mTOR pathway were identified. In vivo, behavior studies revealed that TREM2 could successfully improve ASD mice’s social interaction and cognitive performance. Besides, we discovered that TREM2 could increase autophagy in ASD mice. In vitro, overexpressing TREM2 reduced the expression of PI3K/AKT/mTOR pathway proteins, whereas knocking down TREM2 increased the expression of PI3K/AKT/mTOR pathway proteins. In conclusion, TREM2 could inhibit PI3K/Akt/mTOR signaling pathway, enhance autophagy, and improve the social communication ability and cognitive function of ASD mice.